Putusan Pembatalan Pernikahan karena Disabilitas Suami - Novela, Chikita Catur (Asian Journal of Law and Humanity, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife, with the aim of forming a harmonious family full of love and affection (sakinah, mawaddah, and rahmah). However, in practice, not all marriages run as expected, especially when dishonesty occurs before or during the marriage contract. This study examines the annulment of marriage based on Decision Number 210/Pdt.G/2024/PA.Pkl, filed by a wife after learning that her husband had special needs (mental disabilities) that he had hidden before the marriage. The purpose of this study is to analyze the legal considerations of the panel of judges in granting the annulment request, with a focus on the element of fraud (tadlis) within the framework of Islamic law and Indonesian positive law. The research method used is a normative juridical approach, with data sources in the form of primary legal materials such as the Marriage Law and the Compilation of Islamic Law (KHI), as well as secondary legal materials such as academic literature and court decisions. The results of the study indicate that the concealment of the husband's mental condition fulfills the elements of fraud as regulated in Article 71 letter b of the KHI. The judge considered this act detrimental to the wife and contrary to the fundamental purpose of marriage. Under both Islamic and Indonesian law, fraud related to physical or mental disability is a valid reason for annulment.